Comparison of CKMB, Lactate Levels and Ejection Fraction with Warm and Cold Cardioplegia on First Post Operative Day in Elective CABG Cases - Tufail Ahmad, Sobia Siddique, Abubakar Sadiq, (Pakistan Journal of Medical & Health Sciences, 2022)
Objectives: The main objective of the study is to find the comparison of CKMB, Lactate levels and ejection fraction with warm and cold cardioplegia on first post OP day in elective CABG cases. Material and methods: This cross sectional study was conducted in Armed forces institute of cardiology AFIC /NIHD Rawalpindi during 1st October 2022 to 30th November 2022. Data was collected with the permission of ethical committee of hospital. The study variables were included level of troponin I during intraoperative and post-operative period, time taken for cardiac standstill, CKMB, Lactate levels and ejection fraction with warm and cold cardioplegia, post-operative improvement in ejection fraction, number of days in ICU. Results: The data was collected from 100 patients. There was no statistically significant difference between the two groups as regards bypass and cross clamp times. Mean age of group I patients was 61.3 ± 12.5 years and for group II patients was 67.4 ± 10.4 years. P value of serum lactate level is <0.01, which is statistically significant. All the patients had elevated lactate level but the range of increase in lactate level was seen in those who didn’t take adenosine as compared to those who took adenosine. Practical Implications: Enzymes play an important role in both cold and warm cardioplegia. Conclusion: It is concluded that there is less cardiac enzymes release after the application of warm blood cardioplegia for myocardial protection in patients undergoing CABG as compared to cold crystalloid cardioplegia. Keywords: Cardioplegia, CKMB, Troponin, CABG, Cold